Ethiopia : Focusing Public Expenditures on Poverty Reduction, Voume 2. Appendixes and Statistical Tables - World Bank (Washington, DC, 2013)
The topics for this review were determined by the Government in consultation with a core group of donors at a workshop in Brussels organized by the European Commission in November 2000. The Government suggested reviewing public expenditures at the regional level, starting with three regions. This public expenditure review (PER) marks the first explicit attempt at Regional PERs. This integrated report draws on draft reports from the January-April 2000 mission as well as from a workshop held in Addis Ababa during September 17-18, 2001. The theme amd the focus topics for this PER emerged out of consultations between the Ethiopian governmentand a core donor group at a workshop in Brussels organized by the European Commission in November 2000. This PER is set on three premises: 1) It is thematically set in the context of the Poverty Reduction Strategy Paper and the Heavily Indebted Poor Countries document; 2) It focuses on getting a better understanding of the budgetary institutions, systems and processes at the regional level; and 3) the PER analysis and recommendations are intended to harmonize with the sequence and pace of the Government of Ethiopia's Expenditure Management and Control Program.